Gliotoxin: Nature's Way of Making the Epidithio Bridge1. Issue 13 (24th February 2014) - Amatov, Tynchtyk; Jahn, Ullrich
<x xml:space="preserve">Abstract</x> GliTzy biosynthesis! A detailed picture of the key transformations during the biogenesis of gliotoxin has recently been created. Almost every intermediate in the biosynthetic pathway and the pertinent enzymatic machinery was isolated and fully characterized, thus placing the unique incorporation of the sulfur atoms as well as the formation of the epidithio bridge catalyzed by the key enzyme GliT and its consequences into the limelight.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>